Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.4103/gmit.gmit_118_22
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparison of Conventional Pap Smear and Liquid-Based Cytology for Cervical Cancer Screening

Abstract: Objectives: Early diagnosis and treatment of preinvasive lesions have made cervical cytology one of the most effective methods of cancer screening in industrialized nations, which have seen a sharp decline in the incidence and death of invasive cancer. The aim of this study is to compare liquid-based cytology (LBC) and conventional Pap on cervical smears. Materials and Methods: From July 2018 to June 2022, 600 patients were included in this cross-sectional study, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(52 reference statements)
0
3
0
2
Order By: Relevance
“…These two methods have been compared in many comparative studies that provided conflicting results [20][21][22][23][24][25][26][27]. In 2008, Arbyn et al published a meta-analysis of eight studies and reported no difference between CC and LBC in terms of sensitivity and specificity for the detection of high-risk lesions [19].…”
Section: Conventional and Liquid-based Cytologymentioning
confidence: 99%
“…These two methods have been compared in many comparative studies that provided conflicting results [20][21][22][23][24][25][26][27]. In 2008, Arbyn et al published a meta-analysis of eight studies and reported no difference between CC and LBC in terms of sensitivity and specificity for the detection of high-risk lesions [19].…”
Section: Conventional and Liquid-based Cytologymentioning
confidence: 99%
“…From a clinical perspective, the use of LBC can reduce the need for repeat testing due to unsatisfactory samples, leading to faster diagnosis and treatment initiation 32 . The possibility of performing HPV DNA testing and other molecular tests on the same sample can provide a comprehensive understanding of the disease, aiding in personalized patient management 33 .…”
Section: Implication For Patient Managementmentioning
confidence: 99%
“…In the article titled “A Comparison of Conventional Pap Smear and Liquid-Based Cytology for Cervical Cancer Screening”, published on pages 77-82, Issue 2, Volume 12 of Gynecology and Minimally Invasive Therapy,[ 1 ] the list of authors and affiliations is incorrectly written as:…”
mentioning
confidence: 99%